ANALISIS YURIDIS PELAKSANAAN PEMBINAAN KEMANDIRIAN WARGA BINAAN PEREMPUAN (STUDI PENELITIAN DI LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS IIB BATAM) - Crisya Grace Thessalonika Aritonang; Ramon Nofrial; Lia Fadjriani (Ensiklopedia of Journal, 2022)
Prisons are no longer seen as places of punishment only, but also as a training for fostered citizens. The scope of coaching for fostered residents is divided into two areas, namely Personality Coaching and Independence coaching. This research is important to be carried out in order to find out how the Batam Class IIB Women's Correctional Institution carries out self-reliance development even though Batam does not yet have its own building and does not yet have the trainers needed as facilities and infrastructure that will be used to carry out activities to foster the independence of women-assisted residents. This research uses normative and empirical methods where data collection is used by taking legal and statutory approaches that are the basis of the law, and conducting direct interviews with the Head of the Work Activities Sub-Section of the Batam Class IIB Women's Correctional Institution and residents. The results of this research show that the legal arrangements carried out by the Batam Class IIB Women's Correctional Institution are in accordance with the applicable regulations, namely the Law of the Government Regulation of the Republic of Indonesia Number 31 of 1999 concerning the Development and Guidance of Correctional Assisted Citizens. The obstacle factor is the Batam Class IIB Women's Correctional Institution does not yet have its own building and does not have trainers. The suggestion in this study is that training of work unit officers is also needed because they also have the task and function of providing guidance in the work unit so that special knowledge or skills are needed for them. With that, it can help the implementation save more budget because it is not needed to bring in instructors from outside because the officers themselves already have qualified expertise.